The cis‐regulatory switchboard of pancreatic ductal cancer. (18th February 2016) - Ferrer, Jorge; Real, Francisco X
Abstract : Pancreatic ductal adenocarcinoma (PDAC) remains one of the most devastating human diseases. There is consequently a pressing need to understand its molecular underpinnings, which should enable new preventive and therapeutic strategies. A new study in The EMBO Journal (Diaferia et al, 2016) maps the transcriptome and epigenetic landscape associated with distinct PDAC grades and identifies cis ‐ and trans ‐regulatory elements in tumour progression. Abstract : A new genomewide study identifies cis ‐ and trans ‐regulatory elements in pancreatic ductal carcinoma, thus shedding light on the mechanisms underlying tumour progression.